2020
DOI: 10.3390/ijerph17145091
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Combined Training in Idiopathic Pulmonary Fibrosis: A Case Study

Abstract: A supervised combined training program was applied to a sedentary 56-year-old man with idiopathic pulmonary fibrosis (IPF) along three years, until lung transplantation. It included: (a) aerobic continuous (CT) and interval training (IT), (b) high load resistance training (RT) and (c) inspiratory muscle training (IMT). IT and IMT were applied for two years, while CT and RT could be maintained until transplantation using supplemental oxygen. Maximal inspiratory pressure (MIP) kept above 180 cm H2O and forced vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
(57 reference statements)
0
3
0
1
Order By: Relevance
“…It is important to consider and precisely determine the fundamental principles of the selection of the charge—including the level of the inspiratory resistance applied, its frequency and the duration of the training units, with its placement within the training cycle of the athletic field—as the effects of IMT on RM are contingent on these principles [ 26 ]. Recent studies surrounding IMT and its repercussion on health [ 12 , 13 , 27 , 28 ], as well as its athletic performance [ 7 , 20 , 26 ] and the articles included in this study [ 4 , 9 , 11 , 16 , 19 , 25 ], follow the recommended guidance of PwB [ 3 ], which recommends the execution of 30 maximal inspirations twice a day to specifically strengthen inspiratory muscles and obtain the benefits derived from said fortification as health and/or physical endurance improvements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to consider and precisely determine the fundamental principles of the selection of the charge—including the level of the inspiratory resistance applied, its frequency and the duration of the training units, with its placement within the training cycle of the athletic field—as the effects of IMT on RM are contingent on these principles [ 26 ]. Recent studies surrounding IMT and its repercussion on health [ 12 , 13 , 27 , 28 ], as well as its athletic performance [ 7 , 20 , 26 ] and the articles included in this study [ 4 , 9 , 11 , 16 , 19 , 25 ], follow the recommended guidance of PwB [ 3 ], which recommends the execution of 30 maximal inspirations twice a day to specifically strengthen inspiratory muscles and obtain the benefits derived from said fortification as health and/or physical endurance improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been suggested that other physiological mechanisms could explain the ergogenic effect of the IMT: diaphragm hypertrophy, an increase of the sanguine flow to locomotor muscles, a diminution in the subjective blood flow, reduction of fatigue, decreased dyspnoea, an increment in the efficiency and respiratory endurance, an alteration in the composition of muscular fibres to type I and augmentation of fibres type II in intercostal muscles, optimization of neuro-motor control in respiratory muscles maintaining the production of pressure with a minor motor impulse and a higher economization of the respiratory muscles [ 11 ]. Moreover, IMT is employed as a treatment for patients with respiratory condition—such as asthma, dyspnoea, and chronic obstructive pulmonary disease—with a better standard of living of the patients as a result [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…(39) Outro relato de caso demonstrou que treinamento aeróbio intervalado, treinamento de resistência e TMI em longo prazo ajudaram a manter a independência funcional, capacidade de caminhar e tolerância ao treinamento de resistência em um homem de 56 anos até o declínio da capacidade funcional em virtude da FPI. (40) Foram incluídos nesta revisão de escopo 3 resumos que relataram os efeitos do TMI na DPI. Kerti et al (41) buscaram investigar os efeitos do TMI com RP em parâmetros funcionais e na qualidade de vida em pacientes com DPI.…”
Section: Efeitos Do Tmi Separadamente Ou Com Rpunclassified
“…In a case report, VO 2 peak increased at 1.5 years after a supervised combined exercise training program in a man with IPF, remaining above the level of poor prognosis at 2 years. [44] However, due to limited data, we could not explore the long-term effects of exercise training on VO 2 peak. Vainshelboim’s study suggested that the influence of supervised exercise training on VO 2 peak was different from that of unsupervised exercise training.…”
Section: Discussionmentioning
confidence: 99%